Monascus red pigment influence on hydroxyapatite nanoparticles-mediated renal toxicity in rats - Nasser N. Alqurashy; Mokhtar I. Yousef; Ahmed A. Hussein; Maher A. Kamel; Abeer El Wakil (Scientific Reports)
Abstract Hydroxyapatite nanoparticles (HANPs) have been applied in several biomedical fields. However, its interaction with biological systems is less exploited. This study aimed to characterize HANPs, examine their influence on kidneys, and explore the potential protective effects of naturally extracted red pigment (RP) from Monascus purpureus against HANPs-induced renal toxicity. To this aim, forty eight adult male rats were randomly divided into 8 equal groups: a control group receiving 4% dimethyl sulfoxide (the solvent for HANPs), three groups receiving extracted RP at different doses of 10, 20, and 40 mg/kg, a group receiving HANPs at a dose of 88.3 mg/kg, and three more groups receiving a double treatment of HANPs associated with RP. The respective treatment was given daily by oral gavage to animals for 50 days which is the duration of the whole experiment. The renal toxicity caused by HANPs was manifested by aberrations in kidney function parameters, intensification of oxidative stress markers, and a decrease in the activity of antioxidant enzymes. Moreover, an increase in inflammatory (TNF-α and TGF-β) and apoptotic (caspace-3) markers, an elevation in gene-based kidney injuries markers (Kim-1 and lipocalin-2), and pathological tissue changes were determined. Meanwhile, co-treatment with different doses of biopigment and HANPs have reduced oxidative stress via their potent antioxidant effect. This was confirmed by pronounced improvement in the measured parameters along with the histological structural enhancement in a dose dependent manner compared to controls. To sum up, RP from M. purpureus has potential protective benefits in mitigating the adverse effects of HANPs.